Pembagian Beban Menggunakan PCC dan Failover Recursive Gateway di Jaringan Komputer Lingkungan SMK Al-Munawaroh Cianjur - Dedi Dedi; Alkautsar Rahman (Universitas Kebangsaan Republik Indonesia, 2024)
The A stable and efficient internet network is crucial to support the teaching and learning activities in educational institutions such as SMK Almunawwarah. However, challenges such as limited bandwidth and reliance on a single Internet Service Provider (ISP) often lead to network instability. This study implements load balancing using the Per Connection Classifier (PCC) method and a Failover Recursive Gateway system on a Mikrotik router to address these issues. The PCC method is used to evenly distribute network traffic across multiple ISP connections based on IP addresses, ports, and other parameters. Meanwhile, the failover recursive gateway ensures continuous connectivity by automatically switching traffic to a backup ISP when one ISP experiences downtime. This implementation successfully improves network stability, maximizes bandwidth utilization, and minimizes downtime. The results of the study indicate that with the integration of PCC load balancing and failover recursive, the network performance at SMK Almunawwarah becomes more optimal, thereby better supporting teaching and learning activities.